2020
DOI: 10.1270/jsbbs.19051
|View full text |Cite
|
Sign up to set email alerts
|

Understanding buckwheat allergies for the management of allergic reactions in humans and animals

Abstract: Buckwheat allergy is an immediate hypersensitivity reaction that includes anaphylaxis mediated by specific IgE antibodies. Several IgE-binding proteins in common buckwheat have been reported to be possible clinically relevant buckwheat allergens. Although common buckwheat is popularly consumed in Asia, buckwheat allergy is becoming a serious problem not only in Asia but also in Europe. In addition, common buckwheat has also been found to be a causative agent of allergic symptoms in animals. In recent years, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Moreover, three larger proteins (40, 45 and 48-kDa) were found to be important buckwheat allergens [ 13 ]. Nowadays, allergens in common buckwheat are reported as Fag e 1 (13S globulin), Fag e 2 (2S globulin), Fag e 3 (7S globulin/vicilin), Fag e 4 (antimicrobial peptide), Fag e 5 (vicilin-like protein), Fag e 10 kD (α-amylase inhibitor/tripsin inhibitor) and Fag e T1 (trypsin inhibitor) [ 5 , 7 ]. Fage 1 and Fag e 2 are considered to be the main allergens in common buckwheat [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, three larger proteins (40, 45 and 48-kDa) were found to be important buckwheat allergens [ 13 ]. Nowadays, allergens in common buckwheat are reported as Fag e 1 (13S globulin), Fag e 2 (2S globulin), Fag e 3 (7S globulin/vicilin), Fag e 4 (antimicrobial peptide), Fag e 5 (vicilin-like protein), Fag e 10 kD (α-amylase inhibitor/tripsin inhibitor) and Fag e T1 (trypsin inhibitor) [ 5 , 7 ]. Fage 1 and Fag e 2 are considered to be the main allergens in common buckwheat [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Buckwheat products are sometimes used to feed horses, so-called “horse muesli” [ 7 ]. In one study on specific IgE activity in sera from 51 horses from Europe and Japan, the most prevalent allergy in horses with allergic reactions was against buckwheat.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Geiselhart et al (2018) identified 55 kDa vicilin-like and 3.9 kDa hevein-like antimicrobial polypeptides, recognized as Fag e 5 and Fag e 4, respectively, by the International Union of Immunological Societies (IUIS) allergen nomenclature sub-committee. Fag e 10 kDa (α-amylase inhibitor/trypsin inhibitor, 10 kDa/ 16 kDa) and Fag e TI (Trypsin inhibitor, 7 kDa/ 9 kDa) were also reported ( Satoh et al, 2020 , Heffler et al, 2014 ).…”
Section: Introductionmentioning
confidence: 92%
“…Soba noodle popularity is due to the health benefits associated with buckwheat, such as blood pressure lowering, anticancer and antiageing properties (Gimenez‐Bastida & Zielinski, 2015). However, buckwheat can illicit allergenic reactions (Heffler et al ., 2014; Satoh et al ., 2020). Moreover, the high cost of buckwheat limits its use in food formulations.…”
Section: Introductionmentioning
confidence: 99%